Chronic Exposure to Methylmercury Enhances the Anorexigenic Effects of Leptin in C57BL/6J Male Mice - Ferrer, Beatriz (Food Chem Toxicol, 2020)
Several studies have demonstrated that heavy metals disrupt energy homeostasis. Leptin inhibits food intake and decreases body weight through activation of its receptor in the hypothalamus. The impact of heavy metals on leptin signaling in the hypothalamus is unclear. Here, we show that the environmental pollutant, methylmercury (MeHg), favors an anorexigenic profile in wild-type males. C57BL/6J mice were exposed to MeHg via drinking water (5 ppm) up to 30 days. Our data shows that MeHg exposure was associated with changes in leptin induced activation of Janus kinase 2 (JAK2)/signal transducer and activator of transcription 3 (STAT3) signaling pathway in the hypothalamus. In males, the activation of JAK2/STAT3 signaling pathway was sustained by an increase in SOCS3 protein levels. In females, MeHg-activated STAT3 was inhibited by a concomitant increase in PTP1B. Taken together, our data suggest that MeHg enhanced leptin effects in males, favoring an anorexigenic profile in males, which notably, have been shown to be more sensitive to the neurological effects of this organometal than females. A better understanding of MeHg-induced molecular mechanism alterations in the hypothalamus advances the understanding of its neurotoxicity and provides molecular sites for novel therapies.